High‐Efficiency PbS Quantum‐Dot Solar Cells with Greatly Simplified Fabrication Processing via "Solvent‐Curing". Issue 25 (2nd May 2018) - Lu, Kunyuan; Wang, Yongjie; Liu, Zeke; Han, Lu; Shi, Guozheng; Fang, Honghua; Chen, Jun; Ye, Xingchen; Chen, Si; Yang, Fan; Shulga, Artem G.; Wu, Tian; et al.
Abstract: PbS quantum‐dot (QD) solar cells are promising candidates for low‐cost solution‐processed photovoltaics. However, the device fabrication usually requires ten more times film deposition and rinsing steps, which is not ideal for scalable manufacturing. Here, a greatly simplified deposition processing is demonstrated by replacing methanol with acetonitrile (ACN) as the rinsing solvent. It is discovered that ACN can effectively "cure" the film cracks generated from the volume loss during the solid‐state ligand‐exchange process, which enables the deposition of thick and dense films with much fewer deposition steps. Meanwhile, due to the aprotic nature of ACN, fewer trap states can be introduced during the rinsing process. As a result, with only three deposition steps for the active layer, a CPVT‐certified 11.21% power conversion efficiency is obtained, which is the highest efficiency ever reported for PbS QD solar cells employing a solid‐state ligand‐exchange process. More importantly, the simple film‐deposition processing provides an opportunity for the future application of QDs in low‐cost printing of optoelectronic devices. Abstract : A CPVT‐certified power conversion efficiency (PCE) of 11.21 % (lab champion PCE of 11.84%) for PbS colloidal‐quantum‐dot solar cells is achieved with only three deposition steps for the photoactive layers, benefiting from the "film‐curing" function of acetonitrile as a rinsing solvent.